Development of resistance to FAK inhibition in pancreatic cancer is linked to stromal depletion. Issue 1 (10th May 2019) - Jiang, Hong; Liu, Xiuting; Knolhoff, Brett L; Hegde, Samarth; Lee, Kyung Bae; Jiang, Hongmei; Fields, Ryan C; Pachter, Jonathan A; Lim, Kian-Huat; DeNardo, David G
Abstract : Objective: We investigated how pancreatic cancer developed resistance to focal adhesion kinase (FAK) inhibition over time. Design: Pancreatic ductal adenocarcinoma (PDAC) tumours from KPC mice (p48-CRE; LSL-KRas G12D/wt ; p53 flox/wt ) treated with FAK inhibitor were analysed for the activation of a compensatory survival pathway in resistant tumours. We identified pathways involved in the regulation of signal transducer and activator of transcription 3 (STAT3) signalling on FAK inhibition by gene set enrichment analysis and verified these outcomes by RNA interference studies. We also tested combinatorial approaches targeting FAK and STAT3 in syngeneic transplantable mouse models of PDAC and KPC mice. Results: In KPC mice, the expression levels of phosphorylated STAT3 (pSTAT3) were increased in PDAC cells as they progressed on FAK inhibitor therapy. This progression corresponded to decreased collagen density, lowered numbers of SMA + fibroblasts and downregulation of the transforming growth factor beta (TGF-β)/SMAD signalling pathway in FAK inhibitor-treated PDAC tumours. Furthermore, TGF-β production by fibroblasts in vitro drives repression of STAT3 signalling and enhanced responsiveness to FAK inhibitor therapy. Knockdown of SMAD3 in pancreatic cancer cells abolished the inhibitory effects of TGF-β on pSTAT3. We further found that tumour-intrinsic STAT3 regulates the durability of the antiproliferative activity of FAK inhibitor, and combinatorial targeting of FAK and Janus kinase/STAT3 act synergistically to suppress pancreatic cancer progression in mouse models. Conclusion: Stromal depletion by FAK inhibitor therapy leads to eventual treatment resistance through the activation of STAT3 signalling. These data suggest that, similar to tumour-targeted therapies, resistance mechanisms to therapies targeting stromal desmoplasia may be critical to treatment durability.